Plantando bibliotecas para colher desenvolvimento: análise do Programa de Bibliotecas Rurais "Arca das Letras" no município de Codó - MA - Martins, Carlos Wellington Soares (2013)
Objectively define the light of the literature on regional development framework of the political, social and cultural state of Maranhão and its contradictions with regard to social policies in rural areas, but specifically those relating to literacy and access to cultural goods. This work aims to conduct an analysis of the social policies implemented by the Ministry of Agrarian Development (MDA) with an emphasis on those served by the "Territories of Citizenship." Intends to examine how the spatial dimension, or more precisely the territorial approach to rural development has been incorporated into public policies directed at the Brazilian countryside in recent years. Performs a brief analysis of public policies to encourage reading, but specifically the "Rural Libraries Program Arca das Letras" whose audience rural communities of Maranhão and what the implications on scaling social practices arising from the implementation of program. The research is the search field municipality Codó - MA. To achieve this goal, in addition to readings made, have consulted official documents and information available on the websites of MDA, specifically Portal Citizenship, Department of Agricultural and Community Renewal Arca das Letras, and assess data from the 2006 Census of Agriculture and the 2010 Census and survey Portraits of Reading in Brazil. Performs comparisons between reports released contrast with the reality presented. In the proposed analysis is intended to hear social subjects involved in the process to identify possible distortions of the project, strategies must be redefined in order to ensure that the resource is well used by municipalities and the public policy of encouraging the reading reaches its goal main supply to the various segments of society information and knowledge that will strengthen their citizenship. Notes that the democratization of access to information is configured as an important factor for the individual to feel part of building a society of social relations through providing local development.